Analisis Pemberian Ekstrak Rumput Kebar (Biophytum Petersianum Klotzsch) Terhadap Kadar MDA Mencit Model Diabetes Melitus : Analisis Pengaruh Pemberian EKstrak Rumput Kebar (Biophytum petersianum Klotzsch) terhadap kadar MDA mencit model diabetes melitus - DJURUMANA, YOHANA; MINNALIA SOAKAKONE; YOWAN EMBUAI (Hang Tuah Medical Journal, 2025)
Diabetes mellitus is a group of metabolic disorders characterized by hyperglycemia and abnormalities in the metabolism of carbohydrates, fats, and proteins. The mechanisms of diabetes mellitus can affect infertility starting with an increase in free radicals due to hyperglycemic conditions, leading to glucose auto-oxidation, protein glycation, and activation of the polyol pathway metabolism, which further accelerates the formation of reactive oxygen species. Oxidative stress increases the amount of Reactive Oxygen Species (ROS), oxidizes unsaturated fatty acids in spermatozoa membranes, leading to a chain reaction in cell membranes and the formation of toxic lipid peroxides. Lipid peroxides generate aldehyde compounds due to the disruption of the fatty acid chain, such as Malondialdehyde (MDA). Malondialdehyde (MDA) is a marker of oxidative stress. This study aims to evaluate the effect of Kebar Grass extract on the level of MDA (malondialdehyde), which is one of the indicators of oxidative stress, in a diabetic mouse model. The mice in this study were divided into two groups: a diabetes control group and a treatment group receiving Kebar Grass extract. The results of the study indicate that the administration of Kebar Grass extract did not have a significant effect on the MDA levels in the diabetic mouse model. Although there was a trend of decreased MDA levels in the treatment group, the difference did not reach a statistically significant level. This research indicates that although Elephant Grass has the potential as a traditional remedy for diabetes management, its effect on reducing oxidative stress, measured by MDA levels, may not be very strong. Further research is needed to better understand the mechanisms of action of Elephant Grass in diabetes management and its impact on oxidative stress.